(untitled) - Charan, Ram (San Francisco, 2008)
Charan reveals exactly what's wrong with corporate leadership development and tells how to make it right. He explains the concept of a leadership "gene pool" and shows how companies can discover just what "DNA" they need to succeed. He also details how to uncover the hidden leaders in a company, when and where to bring in fresh talent, how to coach, measure, and reward leadership, and much more. For CEOs, directors, and anyone involved in leadership development, Leaders at All Levels is an eye-opening guide on how to get succession right.
Keywords: Leadership,Executive succession,Lãnh đạo,Lãnh đạo kế nhiệm; Planning,Kế hoạch